SEMANTIC MODELING OF METAPHOR IN ENGLISH AND UZBEK (KONFERENSIYA, 2025)
In this scientific paper, the semantic modeling of linguistic metaphor units isthoroughly studied in English and Uzbek. Metaphors have been described based onLakoff and Johnson’s (1980) conceptual metaphor theory and a Kövecses (2005)cognitive semantic model through mapping between the source and target domain,conceptual structuring/structure, semantic extension mechanisms, and culturalaspects. The study takes the reader into extremely deep research into thecommonalities, differences and culturally based peculiarities of metaphors thatrepresent emotion, time, intellect, social relations and human character in English andUzbek languages to a greater extent